UPAYA MENINGKATKAN PRESTASI BELAJAR IPS DENGAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS V DI SD N 4 NGRAHO KEDUNGTUBAN BLORA - Sutrisno . (Universitas PGRI Yogyakarta, 2017)
This study aims to determine efforts to improve learning achievement for Social Sciences by using media images in class V in SD N 4 Ngraho Kedungtuban Blora. Thisresearch is a class act. Subjects were all students of class V SD N 4 Ngraho KedungtubanBlora totaling 13 students with male students and female students as much as 6 of 7 students.Object of this research is the media image. Steps PTK includes planning, implementation,observation and reflection. Collecting data in this study with the observation, testing anddocumentation. Data were analyzed using the average and the percentage of completeness. It can be concluded that: (1) use of media images can improve prestasibelajar IPS students.The average value in class V SD N 4 Ngraho Kedungtuban Blora, in the Pre Cycle at 63.26with mastery learning as much as 30.43%, after a study carried out using media imagesincreased in the first cycle the average value becomes 74.34 by learning completenessreached 56.52%. In the second cycle the average value becomes 81.52 with learningcompleteness of 95.65%. (2) an increase in adherence to the learning process and students.From these data it can be concluded that the application of IPS mediagambardapat improvelearning achievement in grade V SD N 4 Ngraho Kedungtuban Blora.Keywords: Media images, academic achievement, IPS